Spinal stab injury with retained knife blades: 51 Consecutive patients managed at a regional referral unit. Issue 9 (September 2015) - Enicker, Basil; Gonya, Sonwabile; Hardcastle, Timothy C.
Abstract Background Spinal stab wounds presenting with retained knife blades (RKB) are uncommon, often resulting in spinal cord injury (SCI) with catastrophic neurological consequences. The purpose of this study is to report a single unit's experience in management of this pattern of injury at this regional referral centre. Methods Retrospective review of medical records identified 51 consecutive patients with spinal stabs presenting with a RKB at the Neurosurgery Department at Inkosi Albert Luthuli Central Hospital between January 2003 and February 2015. The data was analyzed for patient characteristics, level of the RKB, neurological status using the ASIA impairment scale, associated injuries, radiological investigations, management, hospital length of stay, complications and mortality. Results The mean age was 28 ± 10.9 years (range 14–69), with 45 (88%) males (M: F = 7.5:1). The median Injury Severity Score was 16 (range 4–26). RKB were located in the cervical [9, 18%], thoracic [38, 74%], lumbar [2, 4%] and sacral [2, 4%] spine. Twelve patients (24%) sustained complete SCI (ASIA A), while 21 (41%) had incomplete (ASIA B, C, D), of which 17 had features of Brown–Sequard syndrome. Eighteen (35%) patients were neurologically intact (ASIA E). There were 8 (16%) associated pneumothoraces and one vertebral artery injury. Length of hospital stay was 10 ± 7.1 days (range 1–27). One patient (2%) died during this period. Conclusions Stab injuries to the spine presenting with RKB are still prevalent in South Africa. Resources should be allocated to prevention strategies that decrease the incidence of inter-personal violence. All RKBs should be removed in the operating theatre by experienced surgeons to minimise complications.